Fast NGC: A new on-line technique for fuel flow measurement - Leach, F; Davy, M; Henry, M; Malladi, M; Tombs, M; Zhou, F; Gold, M; Pearson, R (Society of Automotive Engineers, 2019)
Knowledge of fuel mass injected in an individual cycle is important for engine performance and modelling. Currently direct measurements of fuel flow to individual cylinders of an engine are not possible on-engine or in real-time due to a lack of available appropriate measurement techniques. The objective of this work was to undertake real-time Coriolis fuel flow measurement using GDI injectors on a rig observing fuel mass flow rate within individual fuel injections. This paper evaluates the potential of this technology – combining Coriolis Flow Meters (CFMs) with Prism signal processing together known as Fast Next Generation Coriolis (Fast NGC), and serves as a basis for future transitions on-engine applications. A rig-based feasibility study has been undertaken injecting gasoline through a GDI injector at 150 bar in both single shot mode and at a simulated engine speeds of 1788 and 2978 rpm. The results show that these injections can, in principle, be observed. In addition a number of features of the Fast NGC system unique to gasoline are discussed, and the repeatability of the technique is preliminarily assessed. The study concludes that the Fast NGC system has the potential to measure individual injector flow rates on-engine in real-time.